Correlation between Leukocyte Count and Blood Sedimentation Rate with C-Reactive Protein in Covid-19 Confirmed Patients at Gresik Regional General Hospital: Hubungan Jumlah Leukosit dan Laju Endap Darah Terhadap C-Reactive Protein pada Pasien Terkonfirmasi Covid-19 di Rumah Sakit Umum Daerah Gresik - Khomaroh, Annisatul; Puspitasari, Puspitasari (Universitas Muhammadiyah Sidoarjo, 2023)
Coronavirus Disease 2019 (Covid-19) is a new type of disease caused by the Severe Acute Respiratory Syndrome Coronavirus-2 (SAR-CoV-2) virus which was previously called Novel Coronavirus (2019-nCov). The spread of Covid-19 is very fast and can cause death. The increase in the number of leukocytes is directly proportional to the clinical severity of Covid-19 patients, which begins with viral invasion of the respiratory tract, then the virus will attack target cells, causing an increase in interleukin-6 which is a polypeptide cytokine and c-reactive protein that will code for leukocyte proliferation. Inflammation is a mechanism to protect from various microorganisms, in the inflammatory process cells will release various pro-inflammatory cytokines including c-reactive protein and fibrinogen. This increase in fibrinogen causes high levels of the erythrocyte sedimentation rate. This study aims to determine the relationship between the number of leukocytes and the erythrocyte sedimentation rate on the value of c-reactive protein in confirmed Covid-19 patients. This type of research uses a cross sectional design with purposive random sampling technique using secondary data. Data collection in this study was carried out in June 2022 at the RSUD Ibnu Sina Gresik Laboratory. Statistical test using Spearman correlation test. This study shows that there is a very strong relationship between the number of leukocytes and c-reactive protein (p = 0.000, r = 0.873) then there is a strong relationship between the erythrocyte sedimentation rate and c-reactive protein (p = 0.000, r = 0.659) in patients Covid-19.